PARADIGMA PENDIDIKAN KARAKTER DALAM PRESPEKTIF MULTIPLE INTELLEGENCE (Telaah Paradigm Character Educational Leardership Teacher) - Asnal Mala (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2020)
This article is qualitative research. Case study approach, descriptive analysis. The source of data in this study is library research, which is the procedure for collecting data from various literatures such as books, articles, scientific journals and related literature studied and observations and interviews. The result of this study is the paradigm of character education in the presprective of Multiple Intellegences. As one of the Islamic educational institutions, the methods and strategies of Multiple Intellegences are used as a solution to change the paradigm of teachers in instilling character education from an early age. The character education model at al-Chusanaini Islamic College is included in the category using methods and strategies based on Multiple Intellegences as evidenced by the discovery of several characteristics of the modern pesantren model including the following: Educational institutions at Al-Chusnaini Islamic College use the 2013 Curriculum in each chapter there is a theme that is discussed and developed typical of the sholeh children's school curriculum. Educational institutions at Al-Chusnaini Islamic College are always inten to conduct psychological examinations Multiple intelligences Research (MIR) is mandatory for new shivas to know the tendencies of students' learning styles. Educational institutions at Al-Chusnaini Islamic College are already in the tahab of application and socialization process in organizing K B M (teaching and learning activities) using methods according to the theme of the lesson and student-centered learning strategies, namely student center learning (SCL) in the classroom. The educational institution at the Islamic College Al-Chusnaini inten conducts studies to teachers (mothers) on actual and contemporary issues such as: book discussions that lead to human problems in character education, early childhood education and development, curriculum K 13, Memorization of short letters in the Qur'an and Hadith.